2013
DOI: 10.1128/mcb.00580-13
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane-Proximal KXGFFKR Motif of α-Integrin Mediates Chemoresistance

Abstract: Cell adhesion-mediated drug resistance contributes to minimal residual disease and relapse in hematological malignancies. Here, we show that adhesion of Jurkat T-acute lymphoblastic leukemia cells to substrates engaging ␣4␤1-integrin or ␣5␤1-integrin promotes chemoresistance to doxorubicin-induced apoptosis. Reconstituted expression of ␣4␦, a truncated ␣4-integrin with KXGFFKR as the cytoplasmic motif, in ␣4-deficient cells promoted chemoresistance to doxorubicin in a manner independent of ␣4-mediated adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 57 publications
(77 reference statements)
2
31
0
Order By: Relevance
“…21, 23, 24 This interaction is dependent on the GFFKR peptide motif found at the juxtamembrane cytosolic tail of α -integrins; thus, we speculated that α -integrin function may modulate surface CRT presentation. To address this, we assessed surface CRT levels for cells plated on integrin substrates.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…21, 23, 24 This interaction is dependent on the GFFKR peptide motif found at the juxtamembrane cytosolic tail of α -integrins; thus, we speculated that α -integrin function may modulate surface CRT presentation. To address this, we assessed surface CRT levels for cells plated on integrin substrates.…”
Section: Resultsmentioning
confidence: 98%
“…Previously, we showed that α 4 δ -expressing cells do not adhere to an α 4 β 1-specific substrate, yet exhibit increased α 4 δ binding to CRT in an adhesion-independent manner. 23 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression levels of CD49d were identified as an adverse risk factor in childhood ALL [69], thereby marking it as a potential therapeutic target. It has been shown that CD49d enhanced chemoresistance to doxorubicin in ALL cells [69] [70] and that adhesion of ALL cells to the bone marrow microenvironment is mediated by CD49d. Several mechanisms for how it may exert its chemoprotective effect have been described.…”
Section: Microenvironment -Leukemia Cells Crosstalk: Cell-cell Interamentioning
confidence: 99%
“…11,12 Integrins, particularly α4β1 and αVβ3, which control trafficking to and lodging of HSCs in the BMME, are also crucial for the persistence of minimal residual disease. [13][14][15] The Berlin-Frankfurt-Munster ALL trial (ALL-REZ BFM 2002) revealed that high expression of α4β1 at first relapse was associated with a poor molecular response to therapy and significantly worse eventfree and overall survival. 16 Based on these and other reports, 17 a concept emerged suggesting that a subpopulation of LSCs are quiescent and exhibit relative drug resistance as a result of enhanced adhesive properties toward bone marrow stroma.…”
mentioning
confidence: 99%